PENGEMBANGAN MEDIA PAPRIKA (PAPAN PINTAR INTERAKTIF PERKALIAN) MATERI PERKALIAN BILANGAN CACAH SAMPAI 100.000 DI KELAS V - Fasza, Dea Fitria; Trimurtini (Joyful Learning Journal, 2025)
This research aims to develop Paprika (Multiplication Interactive Smart Board) to increase the learning outcomes of multiplication of integers up to 100,000 in grade V elementary school students. This research uses the Research and Development (R&D) method with the ADDIE model which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the study were grade V students of the Ki Hajar Dewantara Margoyoso Pati Group, a small group trial at SDN Waturoyo and a large group trial at SDN Purwodadi. Paprika media is made from PVC ID Card size A3+ (32.5 × 48.5 cm) and is used in groups of five students. This medium has two main parts: (1) the concept of place values and properties of multiplication (commutative, associative, distributive), and (2) multiplication methods (repeated addition, long stacking, short stacking). The results of the study showed that Paprika is very feasible to use, with 93.75% material validation and 92.85% media validation. This media has also been shown to be effective in improving learning outcomes, with an N-Gain of 0.74 (high category). The response of teachers and students was very good, 98.21% and 93.6%, respectively. The conclusion of this study is that Paprika is a very feasible and effective learning medium in increasing the learning outcomes of multiplication of numbers of numbers up to 100,000 in grade V elementary school students.